Angiotensin-converting enzyme gene polymorphism in Turkish hypertensive patients and its association with left ventricular hypertrophy - (:unkn) unknown (My University, 2002)
The association between ACE gene polymorphism and left ventricular hypertrophy has been studied in different populations with conflicting results. The aim of this study was to investigate this issue in Turkish patients with essential hypertension. One-hundred and seventeen hypertensive patients and 75 healthy controls were studied. Left ventricular mass indexes were examined by echocardiography and PCR technique was used to analyze ACE gene polymorphism. The distribution for DD, ID and II genotypes was not significantly different between patients (42%, 49% and 9%) versus controls (35%,53% and 12%). Allelic frequencies were also similar in both groups (66 vs 62% for D, and 34 vs 38% for I allele in patients vs controls respectively). The prevalence of LVH was 35% in hypertensive group and the genotypic distribution (DD, ID and II) was not significantly different between patients with and without LVH (41%, 57%, 2% vs 42%, 45%, 13%, respectively). The LVMI was not different among the carriers of the three genotypes; mean values were 113±37 g/m2 in DD; 110±36 g/m2 in ID; and 96±11 g/m2 in II patients (p=0.5). In conclusion, ACE gene polymorphism showed no association with either the occurrence of left ventricular hypertrophy or left ventricular mass in Turkish hypertensive patients.
Keywords: ACE gene polymorphism; Hypertension; Left ventricular hypertrophy